Integrating biodiversity in agricultural intensification : toward sound practices - Srivastava, Jitendra, 1940-; Forno, Douglas, 1946-; Smith, Nigel J. H., 1949- (Washington, D.C. : World Bank, 1999)
This report highlights case studies in which modern and traditional agriculture has successfully transformed to enhance biodiversity without sacrificing yield. Lessons learned from this review help to identify sound practices for designing and monitoring agricultural projects so that they improve rural incomes while safeguarding environmental assets, particularly biodiversity. Suggestions for sound practices include modifications of the policy environment and ways to strengthen research institutions and extension services so that agriculture can be intensified while better protecting and managing biological resources.
Includes bibliographical references (p. 39-41).
oif 11/08/15
Loan
Keywords: Agrobiodiversity conservation; Agricultural development projects; Agricultural intensification; Agrobiodiversity